Impact of Heavy Metal Stress on Antioxidant Mechanisms of Avicennia marina (Forsk.) and Rhizophora mucronata Lamk.: Antioxidant of Avicennia marina (Forsk.) - Shams, Samrina; Ismail, Sarwat; Siddiqui, Muhammad Faheem; Azeem, Muhammad; Saifullah, Muhammad; Rasool, Fayyaz (Biological Sciences - PJSIR, 2021)
Mangrove species are growing in exposed areas which have heavy metal contamination. The safeguard the mangrove ecosystem, it is important to understand their antioxidant responses to heavy metal toxicity. The goal of this study was to determine the effect of multi-heavy metals i.e. (Pb, Cd, Cr and Hg) on two mangrove plants Avicennia marina and Rhizophora mucronata of Indus delta via investigating their antioxidative defence mechanism of leaves and roots. In this regard mangrove seedlings of both species were treated with five different concentrations of four heavy metals and different time durations (15, 30, 45 and 60 days) for ascorbate peroxidase, catalase and superoxide dismutase in leaves and root tissues. The findings indicate that the heavy metals have significantly altered the antioxidant enzyme activities with respect of metals concentration and duration of exposure. With extended exposure higher antioxidant activities was observed in metal treated roots and leaves at higher concentrations. A pronounced stimulation (P<0.001) of CAT activity in both roots and leaves of A. marina occurred after 15 days of stress (38.3 and 26.6 µmol/mg protein/min) at 1 MHM. Our analysis also found that roots have shown greater activity in protecting against reactive oxygen species (ROS). Among the roots of two mangroves SOD activity in marina showed better tolerance towards metals stress (9.26 U/mg protein at 15 MHM) compare to mucronata (6.09 U/mg protein at 10 MHM). APX showed maximum stimulation at 20 MHM in leaves (19.130 µmol/mg protein/min) and at 10 MHM in roots (19.02 µmol/mg protein/min) of A. marina after 30 days metals treated plant. Hence, it confirms that the antioxidative defence system plays a critical role in A. marina and R. mucronata to tolerate the multiple heavy metals stress. However, A. marina showed greater antioxidant activity especially catalyst enzyme activity as compared to R. mucronata, which is well evident by its dominancy in the region.